Ecological speciation in an island snail: evidence for the parallel evolution of a novel ecotype and maintenance by ecologically dependent postzygotic isolation. Issue 10 (18th March 2013) - Stankowski, Sean
Abstract Speciation is the process by which reproductive isolation evolves between populations. Two general models of speciation have been proposed: ecological speciation, where reproductive barriers evolve due to ecologically based divergent selection, and mutation‐order speciation, where populations fix different mutations as they adapt to similar selection pressures. I evaluate these alternative models and determine the progress of speciation in a diverse group of land snails, genus Rhagada, inhabiting Rosemary Island. A recently derived keeled‐flat morphotype occupies two isolated rocky hills, while globose‐shelled snails inhabit the surrounding plains. The study of one hill reveals that they are separated by a narrow hybrid zone. As predicted by ecological speciation theory, there are local and landscape level associations between shell shape and habitat, and the morphological transition coincides with a narrow ecotone between the two distinct environments. Microsatellite DNA revealed a cline of hybrid index scores much wider than the morphological cline, further supporting the ecological maintenance of the morphotypes. The hybrid zone does not run through an area of low population density, as is expected for mutation‐order hybrid zones, and there is a unimodal distribution of phenotypes at the centre, suggesting that there is little or no prezygotic isolation. Instead, these data suggest that the ecotypes are maintained by ecologically dependent postzygotic isolation (i.e. ecological selection against hybrids). Mitochondrial and Microsatellite DNA indicate that the keeled‐flat form evolved recently, and without major historical disruptions to gene flow. The data also suggest that the two keeled‐flat populations, inhabiting similar rocky hills, have evolved in parallel. These snails provide a complex example of ecological speciation in its early stages.